Therapeutic strategies to enhance immune response induced by multiple myeloma cells - Liu, Zhaoyun; Yang, Chun; Liu, Xiaohan; Xu, Xintong; Zhao, Xianghong; Fu, Rong (Frontiers in Immunology, 2023)
Multiple myeloma (MM)as a haematological malignancy is still incurable. In addition to the presence of somatic genetic mutations in myeloma patients, the presence of immunosuppressive microenvironment greatly affects the outcome of treatment. Although the discovery of immunotherapy makes it possible to break the risk of high toxicity and side effects of traditional chemotherapeutic drugs, there are still obstacles of ineffective treatment or disease recurrence. In this review, we discuss therapeutic strategies to further enhance the specific anti-tumor immune response by activating the immunogenicity of MM cells themselves. New ideas for future myeloma therapeutic approaches are provided.